2014
DOI: 10.1002/hipo.22275
|View full text |Cite
|
Sign up to set email alerts
|

Encoding and retrieval of landmark‐related spatial cues during navigation: An fMRI study

Abstract: To successfully navigate, humans can use different cues from their surroundings. Learning locations in an environment can be supported by parallel subsystems in the hippocampus and the striatum. We used fMRI to look at differences in the use of object-related spatial cues while 47 participants actively navigated in an open-field virtual environment. In each trial, participants navigated toward a target object. During encoding, three positional cues (columns) with directional cues (shadows) were available. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 41 publications
9
30
1
Order By: Relevance
“…This result confirmed the first hypothesis that landmark would facilitate successful wayfinding, and; this finding aligns with previous studies (Jansen-Osmann and Wiedenbauer, 2004; Jansen-Osmann and Fuchs, 2006; Wegman et al, 2014). An earlier rodent study (Youngstrom and Strowbridge, 2012) confirmed the pivotal role of landmarks in the spatial representation for successful wayfinding.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result confirmed the first hypothesis that landmark would facilitate successful wayfinding, and; this finding aligns with previous studies (Jansen-Osmann and Wiedenbauer, 2004; Jansen-Osmann and Fuchs, 2006; Wegman et al, 2014). An earlier rodent study (Youngstrom and Strowbridge, 2012) confirmed the pivotal role of landmarks in the spatial representation for successful wayfinding.…”
Section: Discussionsupporting
confidence: 92%
“…Electrophysiological and imaging studies have pointed out the importance of landmarks and their corresponding locations in wayfinding (Jansen-Osmann and Wiedenbauer, 2004; Janzen and Jansen, 2010; Wegman et al, 2014). For example, Janzen and Jansen (2010) showed the involvement of Para-Hippocampal Gyrus (PHG) in object and scene recognition.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that optimal performance in the WMT is based on the use of spatial information provided from visual environmental cues, for example, based on the fixed spatial relationship between the platform and the available visual cues (O'Keefe et al, 1978) or the contributions of visual cues to the selection of trajectories to the platform location (Knierim et al, 2011). The hippocampus plays an integral role in memory function; it is critical for processing spatial and contextual information and for generating and maintaining representations utilized for navigating in space (Jarrard, 1993; O'Keefe et al, 1978; Wegman et al, 2014). To this end, rodents with hippocampal lesions have been shown to exhibit deficits in spatial learning on this task, as evidenced by an inability to efficiently navigate to the hidden platform (Morris et al, 1982; Sutherland et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with right hippocampus damage have shown a selective spatial memory deficit (36). An fMRI study found that good between-participant performance in spatial processing tasks was predicted by right hippocampal activation (37). A volumetric analyses of structural MRI data indicated that the size of right posterior hippocampus predicted the ability to use spatial knowledge to make inferences about the relative positions of different buildings on campus (38).…”
Section: Discussionmentioning
confidence: 99%